(untitled) (Ustozlar uchun, 2025)
The article explores the concept of hybrid intelligence as a key direction in the development of artificial intelligence (AI) systems. It examines the integration of human cognition and machine algorithms into a single cognitive system. The advantages of hybrid models in the context of decision-making, system stability, and interpretability improvement are analyzed. The problems of ethical responsibility, algorithmic transparency, and the culture of human-machine collaboration are discussed. Examples of hybrid intelligence applications in medicine, economics, and industry are provided.The paper concludes with the importance of developing joint cognitive systems as the foundation for responsible AI utilization in the future.